Formulation of Desloratadine Oral Disintegrating Tablets - Mohamed A. Etman, Mona Gamal, Aly H. Nada, Mohamed A. Shams-Eldeen (Journal of Applied Pharmaceutical Science, 2014)
Desloratadine (DS) is a tricyclic antihistaminic, characterized by bitter taste and slight water solubility. The aim of this study is to prepare DS as orally disintegrating tablets (ODT) to mask the bitter taste and improve compliance. Twelve different placebo ODT (F1-F12) were prepared using mannitol as diluent, in addition to functional excipients. The formulations were evaluated for relevant in vitro characteristics. DS powder was treated by different techniques and polymers (hydroxypropyl methyl cellulose (HPMC), Eudragit RL 30, and Eudragit EPO) for taste masking of DS. The placebo and DS- ODT tablets were assessed for taste masking efficiency by a panel of 10 volunteers. All placebo formulations were non sticky except four formulations (F8- F11), and compressible with the exception of F2. F12 showed the least disintegration time (20 sec) without sticking tendency.The compressible non sticky formulations were used for preparation of DS tablets and subjected to further in vitro evaluation. Fairly good weight uniformity values were observed in all the tested ODT formulations. F12 exhibiting the shortest wetting time (14.7 seconds) and the least disintegration time (20 seconds). 100% DS release was attained after 2.5 minDS-ODT, compared to 82% from conventional marketed tablets (Aerius®) at same time interval.
Keywords: Desloratadine, Oral Disintegrating Tablets, In vitro tests, Taste masking